Man Yinager Yenebere... Yetahisasu Girgir Ena Mezezu - Berhanu Aseres (Addis Ababa Univeristy; Addis Ababa :., 2005)
On the 1953 coup and its implcations on Ethiopia.
Includes bibliographical references (pages 442-445). In Amharic.